Thomas M. Patterson, The Charter and Ordinances of the City of Denver 135, § 12 (1875) - (:unkn) unknown (My University, 1875)
Prohibited the keeping in a place of business or elsewhere within Denver, any gun powder or gun cotton exceeding twenty-five pounds at one time. The same shall be kept in tin or copper canisters or cases not exceeding five pounds. Violators fined not less than ten nor exceeding one hundred dollars.
Keywords: GUNPOWDER - STORAGE